2008
DOI: 10.1176/appi.ps.59.9.1056
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Co-occurring Eating Disorders in Publicly Funded Addiction Treatment Programs

Abstract: Objective Publicly funded addiction treatment programs were surveyed to increase understanding of treatment options for persons with co-occurring eating and substance use disorders. Methods Data were collected between 2002 and 2004 from face-to-face interviews with program directors of a nationally representative sample of 351 addiction treatment programs. Results Half of the programs screen patients for eating disorders; 29% admit all persons with eating disorders, and 48% admit persons with eating disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Given the potential clinical relevance of eating disorder symptoms among treatment-seeking women with SUDs, investigators examined data from the National Treatment Center Study (NTCS) [30,31] to enhance understanding of current treatment resources available to patients with co-occurring eating disorders who present for addiction treatment [14,15]. The first analysis focused on a nationally representative sample (n=351) of publicly-funded programs that received more than 50% of their annual operating revenues from federal, state, or local grant sources [14].…”
Section: 0 Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the potential clinical relevance of eating disorder symptoms among treatment-seeking women with SUDs, investigators examined data from the National Treatment Center Study (NTCS) [30,31] to enhance understanding of current treatment resources available to patients with co-occurring eating disorders who present for addiction treatment [14,15]. The first analysis focused on a nationally representative sample (n=351) of publicly-funded programs that received more than 50% of their annual operating revenues from federal, state, or local grant sources [14].…”
Section: 0 Resultsmentioning
confidence: 99%
“…The first analysis focused on a nationally representative sample (n=351) of publicly-funded programs that received more than 50% of their annual operating revenues from federal, state, or local grant sources [14]. Data were collected during on-site visits conducted between January 2005 and August 2006.…”
Section: 0 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, no integrated, evidence-based treatments for EDs and substance-use disorders are available. 30 Like many co-occurring psychiatric conditions, individuals presenting to treatment with substance-use disorders and EDs typically receive treatment in programs specializing in substance-use disorders or EDs. They rarely receive services for both disorders.…”
Section: Role Of Co-occurring Disordersmentioning
confidence: 99%
“…A recent national survey of screening and treatment practices at 351 addiction treatment programs revealed that only half (51%) screen for EDs at intake or assessment, and only 29% admit patients who screen positive for EDs. 30 …”
Section: Role Of Co-occurring Disordersmentioning
confidence: 99%